Pengaruh Efikasi Diri Dan Kontrol Diri Terhadap Prokrastinasi Akademik Siswa SMK Negeri 4 Pandeglang - Hakiki, Reza; Yohana, Corry; Fadillah, Nadya (Jurnal Syntax Fusion, 2022)
The purpose of this study is to determine the influence of self-efficacy and self-control on academic procrastination of State Vocational High School 4 Pandeglang. The research method used is a survey method with a descriptive approach. The samples in this study was 134 respondents. For data processing, researchers processed questionnaires using a likert scale. The variables Academic Procrastination (Y), Self-Efficacy (X1), and Self-Control (X2) are primary data in the form of research questionnaires. Data analysis techniques using multiple linear regression with SPSS program version 2 3.0 it begins by looking for an analysis requirement test using the Kolgomorov-Smirnov normality test with academic procrastination significance results of 0.200, self-efficacy of 0.200, and self-control of 0.200. Then use a linearity test with significance values on the linearity of self-efficacy and self-control of 0.000. Test classical assumptions using heteroskedasticity test in Spearman rho test with variable significance values of self-efficacy of 0.195 and self-control of 0.08 8. The multicholinearity test of self-efficacy and self-control variables had a tolerancre value of 0.9 71 and a VIF value of 1.029. The F test is worth 116.547. and the T test on the self-efficacy variable of -1.861 and the self-control variable of -14.621. The result of the multiple regression equation is as follows Ŷ = 9,817 – 0,163X1 – 0,946X2, From the equation, the influence of self-efficacy and self-control on academic procrastination has an influence in a negative and significant direction. The result of the coefficient of determination (R2) is 0.640 which means that the degree of influence of self-efficacy and self-control on academic procrastination belongs to the very strong classification.